English Learning Based on Open Space for Communities in Tana Toraja District - Nehru Pasoloran Pongsapan (Teaching English as a Foreign Language Overseas Journal, 2019)
The objective of this research is to find out the problem faced by the fourth semester Educators at the university, high school and academy levels have the obligation to carry out the tri-services of tertiary institutions, namely (1) education and teaching, (2) research in the context of developing science and (3) carrying out community service based on the field of science and technology in accordance his/her discipline. Likewise, lecturers in the English Language Study Program, have the competence to carry out "Community Service" in the form of teaching English, both in the form of courses, seminars, workshops, therefore, the English language lecturer of Toraja Indonesian Christian University has implemented the "Community Service" program "Through collaboration with the Government of the Tana Regency Education Office through the Educational Achievement Reward / Incentives program with English Language Teaching activities to the people who live in around 15 Tana Toraja tourism objects, namely Tongkonan Mebali, Sassa ', Potok Tengan, Pango-Pango, Sasana Makale culture, Papa Batu Tumakke, Talando Tallu, Suaya, Tampanggallo, Kambira, Makula ', Lemo, Buntu Burake, Tumbang Datu, and Tilangnga'. The outcomes of this study are (1) actualizing the Tana Toraja district government program "English Speaking Area" launched by Mr. Ir. Nico Biring Kanae, regent of Tana Toraja in 2016 (2) Improved the ability of English communication for the people of Tana Toraja, and (3) produced a prototype of a British village in Tana Toraja.